THE INFLUENCE OF PEDAGOGICAL COMMUNICATIONS ON THE FORMATION PROFESSIONAL COMPETENCE OF FUTURE TEACHERS - V.S. Pikelna (Academy of Cognitive and Natural Sciences, 2008)
The article reveals the main conceptual apparatus of the communication theory, the attention is paid to the means of communication which pédagogues use. The notions "communication" and "intercourse" are analysed comparatively, also the communicative models are considered.